Spirituality and well-being in terminally ill hospitalized adults - Reed, Pamela G. (Research in Nursing & Health, 1987)
Initial research into the significance of spirituality among terminally ill adults was extended. Two hypotheses were examined using three groups of 100 adults matched on age, gender, education, and religious background: a) Terminally ill hospitalized adults indicate a greater spiritual perspective than nonterminally ill hospitalized adults and healthy nonhospitalized adults. b) Spiritual perspective is positively related to well-being among terminally ill hospitalized adults. All 300 participants completed the Spiritual Perspective Scale, Index of Well-Being, and other information. Planned comparisons analysis results supported the first hypothesis; low but significant correlation lent support to the second hypothesis. Differences among groups on recent change in spiritual views also were examined; a significantly larger number of terminally ill adults indicated a change toward increased spirituality than did nonterminally ill or healthy adults.